Effect of LncRNA XIST on Immune Cells of Primary Biliary Cholangitis - She, Chunhui; Yang, Yifei; Zang, Bo; Yao, Yuan; Liu, Qixuan; Leung, Patrick S. C.; Liu, Bin (Frontiers in Immunology, 2022)
Objective: Primary biliary cholangitis (PBC) is an autoimmune disease with significant gender difference. X chromosome inactivation plays important roles in susceptibility to diseases between genders. This work focuses on the differences of LncRNA XIST in several defined immune cells populations as well as its effects on naive CD4+ T cells proliferation and differentiation in patients with PBC. Methods: NKs, B, CD4+, and CD8+ T cells were separated by MicroBeads from patients with PBC patients and HC in PBMC. The expression levels of LncRNA XIST in these immune cells were quantified by qRT-PCR and their subcellular localized analyzed by FISH. Lentivirus were used to interfere the expression of LncRNA XIST, and CCK8 was used to detect the proliferation of naive CD4+ T cells in PBC patients. Finally, naive CD4+ T cells were co-cultured with the bile duct epithelial cells (BECs), and the effects of LncRNA XIST on the typing of naive CD4+ T cells and related cytokines were determined by qRT-PCR and ELISA. Results: The expression levels of LncRNA XIST in CD4+ T cells in PBC patients were significantly higher than those in HC, and were primarily located at the nucleus. LncRNA XIST could promote the proliferation of naive CD4+ T cells. When naive CD4+ T cells were co-cultured with BECs, the expressions of IFN-γ, IL-17, T-bet and RORγt in naive CD4+ T cells were decreased. Conclusion: LncRNA XIST was associated with lymphocyte abnormalities in patients with PBC. The high expression of LncRNA XIST could stimulate proliferation and differentiation of naive CD4+ T cells, which might account for the high occurrence of PBC in female.